Modulating Frontal Networks’ Timing-Dependent-Like Plasticity With Paired Associative Stimulation Protocols: Recent Advances and Future Perspectives - Guidali, Giacomo; Roncoroni, Camilla; Bolognini, Nadia (Frontiers in Human Neuroscience, 2021)
Starting from the early 2000s, Paired Associative Stimulation (PAS) protocols have been exploited in humans to study brain connectivity in motor and sensory networks by exploiting the intrinsic properties of timing-dependent cortical plasticity. In the last ten years, PAS have also been developed to investigate the plastic properties of complex cerebral systems, such as the frontal ones, with promising results. In the present work, we review the most recent advances of this technique, focusing on protocols targeting frontal cortices to investigate connectivity and its plastic properties, subtending high-order cognitive functions like memory, decision-making, attentional, or emotional processing. Overall, current evidence reveals that PAS can be effectively used to assess, enhance or depress physiological connectivity within frontal networks in a timing-dependent way, in turn modulating cognitive processing in healthy and pathological conditions.